Solubility Enhancement of a Poorly Water-Soluble Drug, Amlodipine Besylate and its Formulation Development into Solid Dispersion using Mixed Solvency Concept and Evaluation of Prepared Solid Dispersions - Rajak, Ashutosh (Asian Journal of Pharmaceutics (AJP), 2023)
Introduction: In recent generation, the difficult task is to overcome solubility problems in the formulation development of the drug. The lower water solubility of drugs causes various challenges in developing formulations and the use of harmful organic solvents produces toxicity. So, this problem is overcome by the mixed solvency concept proposed by Dr R.K. Maheshwari in 2009. In this work, amlodipine besylate was chosen as a model drug and solubilizers selected were sodium benzoate, sodium acetate, sodium citrate, sodium caprylate, poloxamer 407, l-lysine, β-cyclodextrins and niacinamide. The solid dispersions are proposed to be formulated using these expectedly safe water-soluble additives as per mixed solvency concept. Materials and Methods: Solid dispersions were prepared using solvent evaporation method, amlodipine besylate was chosen as a model drug and solubilizers selected were sodium benzoate, sodium acetate, sodium citrate, sodium caprylate, poloxamer 407, l-lysine, β-cyclodextrins and niacinamide. The amlodipine besylate used for the preparation of solid dispersion was characterized and identified by UV spectrophotometric analysis, melting range determination and comparative dissolution studies. Results and Discussions: The amlodipine besylate used for the preparation of solid dispersion was characterized and identified by UV spectrophotometric analysis and melting range determination. The observed values were in accordance with the reported values in the literatures. For pre-formulation studies, the solubility studies of the drug were done in different blends. Also, calibration curves in water and 0.1N HCl were prepared. Interaction studies of drug-solubilizers have shown no interaction and incompatibility between drugs and solubilizers. Solubility of amlodipine besylate drug sample was reported in different blends. UV spectrophotometric study of drugs and solubilizers indicated no drug-solubilizer interference at 368 nm. Different blends of solubilizers were prepared by varying their concentrations. Out of these prepared blends, blend V, blend O and blend C were selected on the basis of the drug solubility at 80-90. Different solid dispersions were prepared with different drug and solubilizers ratios. One of three trail batches of solid dispersions were selected for comparative dissolution studies. The formulated solid dispersions were compared with marketed tablet (tablet powder) and pure drug. Summary and Conclusion: The main objective of the present study is to explore the concept of mixed solvency to formulate the solid dispersion of model drug, amlodipine besylate and also to propose mixed solvency concept as a tool to overcome the situation of limiting resources to increase solubility of poorly soluble substances. The drug content and drug release studies were assessed. Based on the above findings, it may be concluded that the solubility and release of a poorly water-soluble drug can be enhanced using various solid solubilizers by the application of mixed solvency concept.